(untitled) (Journal of the College of Basic Education, 2023)
The literary text, especially the poetic, remains an open world in its connotations, shadows, meanings, knowledge and visions. This makes us live with the text in our modern and modern times in a more complex issue, and it is good in its openness to the mythical, masks, worlds of money and new, and premiums. With the aesthetics of the modern poetic text marred by deliberation and cognitive delay, as it was not along with a connected culture mere impressions and subjective influences, after the modern poet experimented with new poetic techniques, the epitome of poetic position and sound impact, and its open suggestive energies, and as long as the literary text, with all its formations, To a new form, in which reading and contemplation depend, in the sects, the trughat, the trughat, and the slicing of letters and the silence of other text formations that are distracted by the aesthetics of poetic formation (). And a global view.